Preparation of a new formulation of hybrid GNP/Ag conductive ink with a specific ratio of organic solvent - Salim, Mohd Azli; Abu Bakar, Mazilah; Masripan, Nor Azmmi; Photong, Chonlatee; Chew, Kit Wayne (Penerbit Akademia Baru, 2024)
his paper presents the preparation of a new formulation of hybrid GNP/Ag conductive ink with a specific ratio of organic solvent to optimize the properties of hybrid conductive ink. The GNP/Ag hybrid conductive ink was formed with a different ratio of organic solvents which are 33:67,60:40,67:33 and 40:60 of 1-butanol to terpinol which the ratio of conductive filler is higher than the organic solvent. The performance of each ink was examined in terms of bulk resistance and resistivity where the conductive ink was prepared on the copper substrate and cured for five hours in the oven at a temperature of 250°C and underwent a cyclic bending test. Results indicate that the 40:60 ratio of 1-butanol to terpinol is the best ratio for GNP/Ag hybrid conducive ink with a bulk resistance of 0.600Ω and resistivity of 3.6x10-4Ωm. For further exploration, the curing time should remain five hours at a different curing temperature.